PROPUESTA DE INTERVENCIÓN COMUNITARIA PARA POTENCIAR LA PARTICIPACIÓN CIUDADANA EN TORNO AL EJERCICIO DE LOS DERECHOS DE NIÑOS-NIÑAS Y ADOLESCENTES EN EL CANTON SARAGURO PROVINCIA DE LOJA - Paccha Suing, Digna Agustina (2016)
The "proposal of intervention community for enhance LA participation citizen on the exercise of the rights of children and ADOLESCENTS in the CANTON SARAGURO province of LOJA", was carried out on the basis of the principle of community self-development, to which it was necessary to meet the objectives set, including: the theoretical and methodological Foundation from this principle, whereas citizen participation as the main shaft on which is apuntalaran the proposed objectives for this research; "" that makes the exercise, the guarantee of the rights of ninas-ninos in the Saraguro Canton, province of Loja ", resulting in the proposal of Community intervention aimed at promoting citizen participation around the exercise of the rights of ninas-ninos in Saraguro, province of Loja" as a reference from the approach of community self-development, from the local municipality institutions , Canton of childhood and adolescence, and the different ministries Council garantistas of rights to these priority groups. . The investigative work search to generate conditions, social, political spaces, which allow the children and adolescents, increasing participation, that their voice is heard that their proposals, relevant issues are inserted in the planes-programas and projects of State agencies, such as governing bodies of public policy, with a joint inter-agency what allows true participation with intercultural and inclusive approach. The "proposal of intervention community for enhance LA participation citizen on the exercise of the rights of children and ADOLESCENTS in the CANTON 4 SARAGURO province of LOJA", was carried out on the basis of the principle of community self-development, to which it was necessary to meet the objectives set, including: